Therapeutic Drug Monitoring of HIV Antiretroviral Drugs in Pregnancy: A Narrative Review. Issue 2 (April 2020) - O'Kelly, Brendan; Murtagh, Ross; Lambert, John S.
Abstract : Abstract: To date, therapeutic drug monitoring (TDM) has played an important role in the management of pregnant HIV patients on highly active antiretroviral therapy. Historically, in pregnant women living with HIV, the third agent in triple therapy has been either non-nucleoside reverse transcriptase inhibitors or protease inhibitors (PIs). PIs have been the preferred agents because of their robustness from the perspective of viral resistance and the dominant drug class for the management of HIV during pregnancy for the previous decade. As with many drugs used during pregnancy, pharmacokinetic changes decrease exposure to these agents as the pregnancy progresses. This can lead to viral escape at the time of pregnancy and ultimately increase the risk of mother-to-child transmission (MTCT) of HIV. TDM has been well-established for this class of highly active antiretroviral therapy, and appropriate dose adjustment studies have been performed. At present, there is a shift from the traditional treatment paradigm in pregnancy to a new drug class, integrase strand transfer inhibitors (INSTIs). Although INSTIs are affected by pharmacokinetic changes during pregnancy, they do not harbor the same issues with viral escape as seen with PIs at birth and in general eliminate the need for boosting with additional agents like ritonavir (r) and cobicistat (c) [bar elvitegravir (EVG)] that can lead to interactions with treatment of other common infections in HIV, including tuberculosis. Furthermore, INSTIs are the most successful medication for rapidly reducing the viral load (VL) in HIV patients, a useful factor where VL may be unknown, or in late presenters. These merits make INSTIs the best choice in pregnancy, although their use has been hindered in recent years by a report of neural tube defects from a large African study with dolutegravir (DTG). New data from Botswana and Brazil indicate that this risk is less significant than previously reported, necessitating further data to shed light on this critical issue. Current international guidelines including DHHS, EACS, WHO, and BHIVA (for patients with VLs >100, 000 copies/mL or late presenters) now recommend INSTIs as first-line agents. The role of TDM in INSTIs shifts to cases of insufficient viral suppression with standard adherence measures, cases of drug–drug interactions, or cases where EVG/c is continued throughout pregnancy, and thus remains an important aspect of HIV care in pregnancy.